Kepribadian Tokoh Ayah dan Anak dalam Novel Ayah dan Sebelas Patriot Karya Andrea Hirata: Kajian Psikologi Carl Gustav Jung - Hamdiah, Magfirotul; Wahyu Utomo, Mohammad (LPPI Universitas Al-Qolam Malang, 2020)
This study aims to analyze the novel of Ayah and Sebelas Patriot by Andrea Hirata based on Carl Gustav Jung's personality concepts, namely personality structure, personality dynamics, and personality development. Through personality, the analysis will be known as the forms of behavior, feelings, and thoughts of a father and son in interacting. It can describe a person's personal development and the influence of personality formation. The approach used in this study is qualitative. The data source in this study is the novel Ayah and Sebelas Patriot. The data of this study are: (1) the personality structure of father and son figures in the Ayah and Sebelas Patriot by Andrea Hirata; (2) personality dynamics of father and son figures in the Ayah and Sebelas Patriot Novels by Andrea Hirata; and (3) The development of the personality of the father and son characters of the Ayah and Sebelas Patriot Novels by Andrea Hirata. Data collection techniques in this study using document techniques. Based on the results of the study, the personality in the novel Ayah and Sebelas Patriot by Andrea Hirata illustrates the first, personality structure of father and son characters who use feelings and thoughts as a form of behavior. Second, personality dynamics in the novel of Ayah and Sebelas Patriot by Andrea Hirata illustrate the focus of solving problems and conflicts that exist is a form of interaction between personality structures, during the actual power of feeling and attention as a form of psychic energy. Third, personality development in the novel of Ayah and Sebelas Patriot by Andrea Hirata contains personality development focused on problem-solving. The problems faced will make the character's personality better in terms of attitudes and behavior—psychiatric and emotional interactions in humans resulting from personality development. Keywords: Personality, personality structure, personality dynamics, personality development.